PENGARUH KONSENTRASI ION Pb2+ TERHADAP DAYA SERAP KULIT KACANG TANAH, SEKAM PADI DAN SERBUK GERGAJI - Arif Setiawan, Andi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2013)
This research study aims to assess the effect of Pb2+ ion concentration on the adsorption bioadsorben derived from waste biomass in the form of peanut shell, rice husk and sawdust. This research forms a laboratory experiment with a completely randomized design 2 factor. Factor 1: variation of Pb2+ ion concentration of 0.1, 1, 10, 100 and 1000 ppm. As well as the 2 factors: the type bioadsorben: peanut shell, rice husk and sawdust. Examination of the amount of adsorbed Pb2+ ions using Spectofotometer Atomic Absorption (AAS). Adsorption results showed that the greater the concentration of Pb2+ ions, the greater the ions absorbed by bioadsorben. Optimum absorption concentration at each bioadsorben achieved at 10 ppm, with the value of each absorption is greatest in rice husk 4.036 x 10-3 mg/g, followed by sawdust 3,810 x 10-3 mg/g and a peanut shell 2.819 x 10-3 mg/g. Analyysis of 2 factor analysis showed the presence of intereaksi between Pb 2+ ion concentration variations and types of adsorbents for Pb 2+ ions are adsorption.Â Key words : Consentration, ion Pb2+, peanut shell, rice husk and sawdust